Solar photovoltaic self-consumption in the UK residential sector: New estimates from a smart grid demonstration project. (July 2018) - McKenna, Eoghan; Pless, Jacquelyn; Darby, Sarah J.
Abstract: The economic incentive to install a solar photovoltaics ('PV') system depends increasingly on using PV generation on-site ('self-consumption') rather than receiving payments from generating solar energy and exporting it to the grid. There is, however, remarkably little empirical evidence on self-consumption. This paper begins to address this gap by analysing one-minute electricity monitoring data for 302 households that participated in a UK smart grid demonstration project. We calculate annual self-consumption levels and find that they are 855 kWh/year per household on average, or 45% of PV generation. We conduct a simple regression analysis to estimate self-consumption and use the results to show that self-consumption for an average UK household with electricity demand of 4000 kWh/year and 2.9 kWp PV system would be 966 ± 38 kWh/year, equivalent to a 24% reduction in average annual electricity demand from the grid. Our methodology can be readily applied to measure and predict self-consumption in other solar markets as well, which has increasingly important implications for valuing solar investments, setting feed-in tariffs, and examining the impacts of PV on networks and retail sales. Highlights: Self-consumption is increasingly an important driver for solar adoption globally. Empirical evidence of self-consumption from 302 UK households with PV. We find annual self-consumption levels of 855 kWh/year, or 45% of PV generation. Implies electricity bill reduction of 24% for average UK household installing PV. Methodology can be readily applied to other markets.